Fertility Implications of Policy Granting Legal Status Based on Offspring's Nationality - Catalina Amuedo-Dorantes; Cristina Borra; Noelia Rivera Garrido (Institute of Labor Economics (IZA), 2019)
We examine the fertility impact of a change in immigration policy granting temporary legal status to undocumented immigrants based on their offspring nationality. The policy, intended to facilitate family reunification, was enacted in a 2011 Royal Decree in Spain. It recognized the ability for undocumented parents to become temporary legal residents if they had a Spanish child under the age of 18. Using data from the Spanish Labor Force Survey for the 2007 through 2016 period, along with a quasi-experimental approach that exploits the change in legal residency eligibility requirements, we show that the 2011 Royal Decree increased fertility among individuals potentially affected by the reform by approximately 32 percent.
Keywords: J13; J15; K37; 330; immigrants; legalization; fertility; Spain